Conflit, choix et signification - Picavet, Emmanuel (Filosofia, 2023)
Conflicts involve institutions and hence also the rules through which the institutions get a grasp of both the world around them and their own interactions. This indicates that the connection to principles and to the interpretation of norms plays a potentially important role in the explanation or understanding of conflicts. The choice-interpretation link must be examined. In an interactive setting, choices call for interpretations which pertain to the relevant background principles (their implementation, their respective weights in the determination of actions). Trust in a shared order, for example among States on the international scene, calls for limits to the legitimate interpretations of such principles. Moreover, the intricacy between the description of situations and the interpretation of those norms which give a framing to the interactive processes must be taken into account. Shared descriptions play a role in the evolutive interpretation of benchmark norms, and the agents must pay attention to the fact that the observation and description of their own action impact this interpretation. The relevance for peacekeeping is explored through several examples.